Risk Management in UK Small and Medium Enterprises - Shen, Yijun (2011)
This study focuses on the rationales for risk management and business insurance in UK’s small and medium enterprises (SMEs), the purpose of which is to examine the factors that influence the conduct of a risk assessment and the attitude towards the importance of business insurance. We have prepared a questionnaire and select 1024 respondents from 582 SMEs in UK, asking them a series of questions that includes their attitude towards insurance and risk assessment, attitude towards perceived business threats and main objectives, and firm size, etc. Through using logistic regression, ordered probit regression and OLS regression analyses, our result suggest that risk assessment and insurance are complements, not substitutes. Meanwhile, those SMEs which consider health and safety issue to be important are more likely to have a risk assessment and believe insurance is essential as well. While those firms which face more potential threats would prefer purchasing insurance rather than conducting a risk assessment. However, the result also indicates that the demand of insurance and risk assessment is different for firms with different size (different number of employees).